2014
DOI: 10.5194/hess-18-595-2014
|View full text |Cite
|
Sign up to set email alerts
|

Historical trends in precipitation and stream discharge at the Skjern River catchment, Denmark

Abstract: Abstract.A 133 yr data set from the 1055 km 2 Skjern River catchment in western Denmark has been analysed with respect to precipitation, temperature, evapotranspiration and discharge. The precipitation series have been tested and corrected using the standard normal homogeneity test and subsequently corrected for undercatch. The degree of change in the climatic variables is examined using the non-parametric Mann-Kendall test. During the last 133 yr the area has experienced a significant change in precipitation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
(70 reference statements)
2
24
0
Order By: Relevance
“…These changes could correspond to the construction of flood retention basins started around 1982 (Lammersen et al, 2002) and ecological flooding strategy, which allowed small floods to happen for the rehabilitation of ecological systems in the floodplain, introduced in the upper Rhine from 1989 (Siepe, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes could correspond to the construction of flood retention basins started around 1982 (Lammersen et al, 2002) and ecological flooding strategy, which allowed small floods to happen for the rehabilitation of ecological systems in the floodplain, introduced in the upper Rhine from 1989 (Siepe, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Mann-Kendall's test was performed to confirm the existence of a trend in the annual discharge, precipitation and sediment loads, then the human intervention and climate impacts based on the available information of the catchments were discussed (Wu et al, 2012). Pettitt's method (Pettitt, 1979) can be used to detect the time point of trend alternation and analyze the impacts based on a double mass curve (Gao et al, 2013) or a hydrological model (Karlsson et al, 2014). These nonparametric methods for detecting the signal seem, however, not capable enough of explaining when and how much the system had changed, thus making it still difficult to relate the change to human activities.…”
Section: Introductionmentioning
confidence: 99%
“…As a normal practice, the critical value of Z 1-a /2 for a p-value of 0.05 will correspond to a Z-score of 1.96 (or 95% confidence interval). If |Z| > Z 1-a /2 , then a statistically significant trend is unlikely to exist and the null hypothesis H o is rejected while the alternative hypothesis H 1 accepted (i.e., that there is a significant trend in the data series at a significance level of a (Hisdal et al, 2001;Karlsson et al, 2014).…”
Section: Statistical Testing Procedures 321 Mann-kendall Trend Testmentioning
confidence: 99%
“…Groundwater recharge, drain levels, well abstractions and sea levels were assumed constant over time for practical reasons and to reduce computational time. However, Karlsson et al (2014) showed that recharge has 5 changed significantly in Denmark during the last centuries. Changes in recharge could result in different age patterns (cf.…”
Section: Boundary Conditionsmentioning
confidence: 99%